Growth correlations in apple nursery trees - Tadeusz Jacyna (Annales Horticulturae, 2020)
Growth characteristics of maiden trees of several apple cultivars budded on various rootstock/interstem combinations were examined during the studies conducted in the USA (1994–1995), and in Poland (2001 and 2004). The following tree quality characteristics: parent shoot diameter (TD) and its length (TH), total number of sylleptic shoots (TNS) and cumulative shoot extension (SEG) were measured at the end of each growing season. Correlations of TD ´ TNS, and TH × TNS expressed by coeficient of correlations and calculated at the end of each growing season for tested cultivars were significant in 73 and 27% of the examined cases, respectively. Additional measurements of these characteristics measured every 10 days during the entire season in ‘Gala’ trees on M.9 rootstock showed that on most occasions the correlations of both TD´TNS, and TD × SEG were significant in 62 and 75%, respectively, whereas those of TH × TNS and TH × SEG were significant in 38 and 45% of the examined cases, respectively. A significant correlation found between TD and TNS makes TD a more reliable parameter than TH for estimating nursery apple tree quality and its ability to lateral branching.